Revisiting 15 000 hours: towards sustainable school systems for mental health, well-being and learning - Susan M. Sawyer; Monika Raniti; Rohan Borschmann (BJPsych Open, 2025)
An independent evaluation of The Resilience Project’s School Partnership Program in Australian secondary schools found that longer participation (6+ years) in this whole-school programme was associated with improved student outcomes, including reduced symptoms of depression and anxiety. This commentary aims to: (a) describe whole-school approaches to improving health and well-being, with reference to their historical context and some selected key studies; (b) highlight the lack of data on the effectiveness of whole-school approaches for reducing depression and anxiety; (c) signal the potential benefits of whole-school approaches when sustainably implemented; and (d) reinforce the need for research that examines links between implementation factors and outcomes. Overall, this commentary underscores the value of viewing schools as complex social systems where multiple components can align to enhance mental health and well-being outcomes for students.